Chronic Kidney Disease in Children: A Review - Ashraf, Mohd; Jan, Muzafar; Wani, Khurshid Ahmed; Ahmed, Parvez; Ahmed, Javid; Ahmed, Sheikh Nisar (Journal of Pediatric Nephrology, 2020)
Chronic kidney disease (CKD) in children is a life-consuming ailment with a variable but progressive course. CKD, in particular, the end stage kidney disease (ESKD) affects multiple body systems complexed with secondary complications that significantly and adversely affect the growth, development and quality of life. Although uncommon in children, CKD poses unique challenges to the health care delivery system to manage the primary renal disorders and extrarenal manifestations of CKD along with a heavy socioeconomic burden. Despite the availability of better management tools, there is a rise in incidence and prevalence of pediatric CKD for which wide range short- and long-term planning is inevitable that will lure the medicos to acquire the advanced nephrological training and skills, besides providing quality infrastructure and sustained socio-economic support. Our review is aimed to provide recent advances regarding the evaluation and management of pediatric CKD and its complications.